Serum lactate dehydrogenase to albumin ratio as a predictor of severity in COVID-19 patients - Siddeequa, Ayesha; Volturi, Jyotsna; Fatima, Azmath Kulsum; Suleman, M.D Dawood (International Journal of Research in Medical Sciences, 2022)
Background: COVID-19 infection, discovered in Wuhan, China, engulfed vast population in most of the countries in a very short span, ranging from aymptomatic infection to acute respiratory distress syndrome, multiorgan failures and death. Individual studies on serum lactate dehydrogenase and albumin showed association with severity of disease. The purpose of present study is intended to predict the association of combined lactate dehydrogenase (LDH) to Albumin ratio with severity of COVID-19. Methods: A retrospective observational study was carried on already confirmed cases of covid 19 infection from July, 2021 to December, 2021 in Gandhi hospital, Secunderabad. History, clinical features and laboratory findings including LDH: Alb ratio was noted. Cases with known history of carcinomas, chronic kidney disease, chronic liver/lung disease, coronary artery disease, alcoholics were not included. Cases were divided into mild, moderate and severe based on National clinical management protocol for COVID-19. Data was analyzed using SPSS/Medcalc software. Results: LDH and LDH: Alb ratio was significantly raised with the severity of the disease. The AUC in ROC analysis of LDH: Alb ratio was 0.75 compared to 0.71 and 0.62 individually for LDH & Alb respectively; indicating ratio was superior to that of individual parameters. Conclusion: The present study shows significant correlation between LDH: Alb ratio with severity of COVID-19 infection. LDH: Alb ratio could be an easily available tool to predict COVID-19 severity.